Effect of narrative nursing on improving treatment compliance in patients with coronary heart disease (叙事护理提高冠心病患者治疗依从性的效果观察) - TANG Yunlan (唐云兰); WEI Yanshi (韦艳时) (中西医结合护理)
Objective To investigate the effect of narrative nursing on improving treatment compliance in patients with coronary heart disease (CHD). Methods Totally 53 hospitalized patients with CHD were divided into the control group(n=25) and the study group(n=28). All patients received routine nursing interventions during comprehensive treatment of CHD, and patients in the study group received narrative nursing intervention. A self-made questionnaire was used to measure patient compliance with CHD treatment and satisfaction with nursing service during hospitalization. Results The total rates of compliance with CHD treatment and satisfaction with nursing service in the study group were higher than those in the control group (P＜0. 05). Conclusion Narrative nursing is potentially effective to improve patient compliance with CHD treatment and satisfaction with nursing service, having a positive effect on mental well-being and recovery of patients. (目的 探讨叙事护理提高冠心病住院患者治疗依从性的效果。方法 选取2019年10月—2023年4月医院收治的53例冠心病患者为研究对象, 分为对照组(n=25)和研究组(n=28)。患者住院期间给予冠心病常规治疗方案, 对照组实施常规护理, 研究组在对照组基础上增加叙事护理干预。采用自制量表评估患者住院期间依从性和对护理服务的满意度。结果 研究组患者治疗依从性评价和满意度评价均优于对照组, 差异有统计学意义(P＜0. 05)。结论 叙事护理能提高冠心病住院患者依从性和满意度, 对促进患者康复和心理健康具有积极意义。)